An update on neurocritical care for intracerebral hemorrhage. (3rd June 2019) - Reyes, Ranier; Viswanathan, Meera; Aiyagari, Venkatesh
ABSTRACT: Introduction: Intracerebral hemorrhage remains one of the leading causes of death and disability worldwide with few established interventions that improve neurologic outcome. Research dedicated to better understanding and treating hemorrhagic strokes has multiplied in the past decade. Areas Covered: This review aims to discuss the current landscape of management of intracerebral hemorrhage in a critical care setting and provide updates regarding developments in therapeutic interventions and targets. PubMed was utilized to review recent literature, with a focus on large trials and meta-analyses, which have shaped current practice. Published committee guidelines were also included. A focus was placed on research published after 2015 in an effort to supplement previous reviews included in this publication. Expert Opinion: Literature pertaining to ICH management has allowed for a greater understanding of ineffective strategies as opposed to those of benefit. Despite this, mortality has improved worldwide, which may be the result of growing research efforts. Areas of future research that will impact mortality and improve neurologic outcomes include prevention of hematoma expansion, optimization of blood pressure targets, effective coagulopathy reversal, and minimally invasive surgical techniques to reduce hematoma burden.